Children deciding the family language in Chinese families in multiethnic Malaysia - Teresa Wai See Ong; Su-Hie Ting (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
Chinese parents fail to maintain use of their heritage languages for family communication because their children seem to wield their own power in deciding the home language. Little is known about how micro-language decisions at family level are influenced by macro-societal language use patterns and sociopolitical contexts. This study examined the influence of children’s family language policy on use of heritage languages by Chinese families in multiethnic Malaysia. Data on the language practices, language ideologies, and management strategies of two families were obtained using semi-structured interviews with the mother/father. The findings show that heritage languages prevailed when the children were young. The switch to dominant languages, particularly Mandarin and English, was triggered by the medium of instruction in school. Interestingly, it was the younger children in the family who actively exerted their agency to influence their family language practice in favour of the dominant languages as the means of family communication. The findings indicated that exposure to the heritage language through the media, having grandparents as carers, and parents’ frequent assertions on the value of the heritage language are not sustainable for heritage language maintenance.